Snowman's land [videorecording (DVD)] - Thomson, Tomasz; Thomson, Tomasz; Rimann, Jürgen, 1963-; Wodianka, Thomas; Hermann, Eva Katrin; Schöne, Reiner, 1942-; Kanischtscheff, Waléra (Music Box Films, 2012)
Walter is a professional killer and has bungled a job. Now he has to leave the city and takes up an offer from crime boss Berger to protect his house in a remote region of the Carpathian Mountains. At his side is his old friend Mickey. By accident Berger's young and pretty wife, Sybille is killed and fearing Berger's vengeance, Walter and Mickey decide to hide her body. What at first seemed to be a nice holiday trip for Walter and Mickey soon become a fight for survival for all parties involved.